Exploring women’s visceral engagement with electric appliances in Turkish kitchens - Defne Karaosmanoğlu; Leyla Bektaş Ata; Bahar Emgin (Discover Food)
Abstract This paper investigates the narratives and experiences of women regarding cooking with small electric appliances. It intends to offer a novel perspective on gender and technology studies by foregrounding the visceral dimensions of these encounters. Drawing from a larger project on the historical representations and lived experiences of domestic technologies in Turkey, it highlights how the embodied dimensions of cooking shape the ways women perceive, adapt, and integrate technology into their daily lives. This study is based on interviews with twenty-seven women across five cities in Turkey conducted between 2022 and 2024. While small electric appliances are often marketed for convenience and efficiency, we argue that focusing solely on their instrumental benefits neglects the complex and visceral ways women engage with technology. A visceral approach remains an undervalued lens for understanding these interactions, particularly as women’s embodied knowledge and relationships to kitchen appliances challenge scholarship that prioritizes progress and efficiency. As active agents, many women resist these technologies, viewing them as misaligned with the embodied knowledge and practices integral to cooking. By reevaluating the relationship between food, gender, and technology, we propose that such disengagement challenges the positivist reliance on science and technology, emphasizing the importance of embodied knowledge and everyday practices in shaping women’s interactions with technology.